Directions of Self-Determination and Psychological States of Adolescents - Gularə Karimova Huseynaga (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Self-esteem plays a crucial role in self-education during adolescence. Dissatisfaction with oneself as a result of not conforming to one's own ideals and requirements is played by the realization of shortcomings as an important motive of self-education. Self-education is impossible without analyzing the real self-assessment of the personality according to its individual characteristics, abilities, capabilities and capabilities. Adolescence is the period when he needs to find his "I", the meaning of life. In today's world, psychology can help a teenager optimally go through difficult periods of personality formation. Experience shows that adolescents begin to educate themselves only when they already have a clear account of their actions, there is a need for self-evaluation, understanding of their positive and negative qualities and self-improvement. Usually this happens during adolescence.